2022
DOI: 10.3389/fonc.2022.951662
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemotherapy for the treatment of cutaneous squamous cell carcinoma: The INSPECT experience (2008-2020)

Abstract: IntroductionCutaneous squamous cell carcinoma (cSCC) is a frequent skin cancer with a high risk of recurrence characterized by tumor infiltration and, in advanced cases, a poor prognosis. ECT (electrochemotherapy) is an alternative treatment option for locally advanced or recurrent cSCC that is unsuitable for surgical resection. In this study, we aimed to evaluate the data in the InspECT (International Network for Sharing Practice on ECT) registry of the referral centers and to clarify the indications for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…Regarding quality of life, many studies have reported significant improvement in wellness perception as measured by the EuroQoL 5-dimensions questionnaire, and an important increase in physical and role functioning, with a decrease in pain and fatigue as quantified by the European Organization for Research and Treatment of Cancer core 30 quality-of-life questionnaire. Moreover, the analysis by the EORTC 35-question head and neck cancer-specific module demonstrated an improvement in all domains, in particular regarding the perception of feeling ill, pain, need for pain medication, and mouth opening 11 .…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Regarding quality of life, many studies have reported significant improvement in wellness perception as measured by the EuroQoL 5-dimensions questionnaire, and an important increase in physical and role functioning, with a decrease in pain and fatigue as quantified by the European Organization for Research and Treatment of Cancer core 30 quality-of-life questionnaire. Moreover, the analysis by the EORTC 35-question head and neck cancer-specific module demonstrated an improvement in all domains, in particular regarding the perception of feeling ill, pain, need for pain medication, and mouth opening 11 .…”
Section: Discussionmentioning
confidence: 93%
“…When it comes to tumour size, it has been demonstrated to be inversely proportional to the efficacy of ECT. In particular, Bertino et al 11 demonstrated that smaller lesions (< 3 cm) had better response, ECT was more successful in primary tumours than recurrences or metastases, and pre-treated lesions had worse responses than naïve ones. Specifically, lesions with a diameter ≤ 3 cm had an overall response rate of 88% vs 68% in those with a diameter > 3 cm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The complete and partial response rates were 62% and 21% respectively. Better results were achieved in patients with primary and smaller (< 3 cm) tumors using intravenously administered bleomycin ( 60 ).…”
Section: Electrochemotherapy In Clinical Practicementioning
confidence: 99%